Non-sterilized fermentation of high optically pure d-lactic acid by a genetically modified thermophilic Bacillus coagulans strain - Caili Zhang; Cheng Zhou; Nilnate Assavasirijinda; Bo Yu; Limin Wang; Yanhe Ma (My University, 2017)
Optically pure d-lactic acid (≥ 99%) is an important precursor of polylactic acid. However, there are relatively few studies on d-lactic acid fermentation compared with the extensive investigation of l-lactic acid production. Most lactic acid producers are mesophilic organisms. Optically pure d-lactic acid produced at high temperature not only could reduce the costs of sterilization but also could inhibit the growth of other bacteria, such as l-lactic acid producers. Thermophilic Bacillus coagulans is an excellent producer of l-lactic acid with capable of growing at 50 °C. In our previous study, the roles of two l-lactic acid dehydrogenases have been demonstrated in B. coagulans DSM1. In this study, the function of another annotated possible l-lactate dehydrogenase gene (ldhL3) was verified to be leucine dehydrogenase with an activity of 0.16 units (μmol/min) per mg protein. Furthermore, the activity of native d-lactate dehydrogenase was too low to support efficient d-lactic acid production, even under the control of strong promoter. Finally, an engineered B. coagulans D-DSM1 strain with the capacity for efficient production of d-lactic acid was constructed by deletion of two l-lactate dehydrogenases genes (ldhL1 and ldhL2) and insertion of the d-lactate dehydrogenase gene (LdldhD) from Lactobacillus delbrueckii subsp. bulgaricus DSM 20081 at the position of ldhL1. This genetically engineered strain produced only d-lactic acid under non-sterilized condition, and finally 145 g/L of d-lactic acid was produced with an optical purity of 99.9% and a high yield of 0.98 g/g. This is the highest optically pure d-lactic acid titer produced by a thermophilic strain.
Keywords: Bacillus coagulans; Polylactic Acid; biodegradable polymer synthesis and properties